2018
DOI: 10.2147/ccide.s169438
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-transform infrared spectroscopy/attenuated total reflectance analysis for the degree of conversion and shear bond strength of Transbond XT adhesive system

Abstract: ObjectiveThe objectives of this study were to evaluate the degree of conversion (DC) for Transbond XT curing light of intensity 1,600 mW/cm2 by using variable curing durations and to determine the effect of the tested curing durations adopted in the current experiment on shear bond strength of Transbond XT resin cement.Materials and methodsA total of 85 orthodontic ceramic brackets (Victory series; 3M Unitek) were utilized in the current experiment. The bonding system used in the current study was Transbond XT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…25 In a recent study, Masood et al evaluated the DC for Transbond XT using variable curing durations with 1600 mW/cm 2 light intensity and aimed to determine the effect of the tested curing durations on shear bond strength of the material with ceramic brackets. 26 They found that 6- and 9-seconds curing showed significantly higher shear bond values and better DC when compared to the 3 seconds curing, whereas no significant difference was recorded between the 6- and 9-seconds curing. In this study, the authors concluded that in actual fact, while bonding the ceramic brackets, the irradiation should at least last 6 seconds instead of 3, as advised by the manufacturer.…”
Section: Discussionmentioning
confidence: 95%
“…25 In a recent study, Masood et al evaluated the DC for Transbond XT using variable curing durations with 1600 mW/cm 2 light intensity and aimed to determine the effect of the tested curing durations on shear bond strength of the material with ceramic brackets. 26 They found that 6- and 9-seconds curing showed significantly higher shear bond values and better DC when compared to the 3 seconds curing, whereas no significant difference was recorded between the 6- and 9-seconds curing. In this study, the authors concluded that in actual fact, while bonding the ceramic brackets, the irradiation should at least last 6 seconds instead of 3, as advised by the manufacturer.…”
Section: Discussionmentioning
confidence: 95%
“…The %DC for a resin is defined as the extent to which carbon double bonds (C=C) of the monomer are converted into carbon single bonds (C–C), to form polymers during the polymerization reaction. 23, 24 The FTIR spectroscopy technique employed in this study to investigate the degree of conversion is an essential surface analytical method. The increase in the bond strength values obtained in the current study may be explained by the recorded FTIR spectroscopy values.…”
Section: Discussionmentioning
confidence: 99%
“…The brackets in group MIPW had 3 μl of distilled water applied on top of the FTIR examination window using a microbrush [10]. All specimens were placed under a static load of 100 grams on the FTIR/-ATR examination window [15] as shown in Figure 2 (Thermo Scientific Nicolet iS5 FTIR Spectrometer; Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Attenuated Total Reflectance Fourier Transform Infrared Specmentioning
confidence: 99%
“…All FTIR/ATR measurements were obtained under the following conditions: a resolution of 4 cm −1 and four internal scans per reading [15]. The uncured resin in each group served as the control for the cured resin.…”
Section: Attenuated Total Reflectance Fourier Transform Infrared Specmentioning
confidence: 99%
See 1 more Smart Citation